Peran Instagram @sits_dishubsurabaya sebagai Media Informasi Lalu Lintas di Kota Surabaya - Ananda Nuzulul Maghfiroh (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the role of the Instagram account @sits_dishubsurabaya as a traffic information medium in the city of Surabaya. The background of this study is based on the increasing use of Instagram social media as a means of public communication by government agencies, which enables the rapid, efficient, and easy dissemination of information to the public. The research method used is descriptive qualitative with data collection techniques through observation and documentation of the account's uploaded content. The results show that the @sits_dishubsurabaya account plays an important role in disseminating traffic information, including traffic condition updates, driving safety appeals, and public service announcements. The presentation of content that is visually and substantively informative encourages public engagement through likes, comments, and sharing of posts. These findings show that the effectiveness of social media does not solely depend on the frequency of posts, but on the clarity of the message, the relevance of the information, and interaction with the public. The @sits_dishubsurabaya account plays an important role in supporting the dissemination of public information in the city of Surabaya.